2022
DOI: 10.3390/ijerph192315649
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Psychometric Properties of the Spanish Version of the Measure of Moral Distress for Health Care Professionals (MMD-HP-SPA)

Abstract: Background: The early detection of moral distress requires a validated and reliable instrument. The aim of this study was to carry out an advanced analysis of the psychometric properties of the moral distress scale for health professionals (MMD-HP-SPA) by performing a validation of the construct and its internal and external reliability. Methods: We performed a multicentre cross-sectional study in health professionals belonging to the Andalusian public health system. Construct validity was performed by explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In our study, MD was present in all health professionals with a median of MMD-HP-SPA similar to the latest studies carried out in Spain 14 and Sweden. 15 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, MD was present in all health professionals with a median of MMD-HP-SPA similar to the latest studies carried out in Spain 14 and Sweden. 15 …”
Section: Discussionsupporting
confidence: 89%
“…Regarding these potential negative consequences, the probable association between MD and the propensity to leave a job has been discussed, 14 being relevant that in our sample, more than a third of the doctors and more than half of the nurses considered quit or left their position in the past because of this distress. In addition, a notable percentage of doctors and nursing staff who had needed or thought they needed temporary medical leave due to MD was obtained.…”
Section: Discussionmentioning
confidence: 97%
“…However, Fuji et al found similar psychometric structure in their translation of the scale into Japanese, where they found CFI was 0.91, CFI/TLI 1.02 and RMSEA 0.061 [ 37 ], in line with our translation. Also, in the Spanish version, Girela-Lopez [ 48 ] found a goodness of fit with a CFI at 0.844 and RMSEA at 0.086.…”
Section: Discussionmentioning
confidence: 99%
“…The five dimensions of the scale proposed by Girela-López et al were used: i) Health care, ii) Therapeutic obstinacy-futility, iii) Interpersonal relations of the Health Care Team, iv) External pressure, v) Covering up medical malpractice [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Epstein et al [ 19 ] designed a 27-item MD scale (Measure of Moral Distress for Healthcare Professionals, MMD-HP), revising the earlier MDS-R scale developed by Hamric et al [ 4 ] This instrument has proved its worth in measuring MD and has been validated first in the USA and later in Japan [ 20 ] and Spain [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%